Building customer loyalty through brand trust, service quality, and satisfaction in religious tourism - Ardhani, Zaskia; Rohwiyati, Rohwiyati; Haryono, Tulus; Triatmanto, Boge; Respati, Harianto (International Journal of Innovative Research and Scientific Studies, 2025)
Through this study, the authors try to address the relationship between brand trust (BT), service quality (SQ), satisfaction (SAT), and loyalty (LOY), specifically regarding Maktour Travel and Umrah pilgrims in Indonesia. The study's analysis of Umrah travel industry loyalty is key, as this area has seen a huge surge in fraudulent activity. A quantitative methodology was applied by gathering data from Umrah pilgrims who purchased Maktour Travel services before determining the relationships between the variables using structural equation modeling (SEM). The innovation of the study lies in the integrated model which shows that BT and SQ directly influence loyalty, with SAT acting as a mediator. Thus, the final model presents a different perspective regarding brand trust and service quality in relation to customer loyalty in religious travel. This study emphasizes the significance of travel agencies' future priorities to cultivate long-term customers, particularly in a competitive and often criticized industry, enhancing trust and the quality of services offered. The paper can be beneficial for both the industry and academia by providing insights and recommendations for the Umrah travel industry to enhance their service offerings and relationships with customers. Implication for Theory: For theory, this work adds empirical evidence to the current stream of literature on customer loyalty in tourism, specifically focusing on the nature of trust, service quality, and satisfaction in the context of religious tourism.